Feasibility of dasatinib in children and adolescents with new or recurrent central nervous system germinoma. Issue 9 (10th June 2013) - Osorio, Diana S.; Finlay, Jonathan L.; Dhall, Girish; Goldman, Stewart; Eisenstat, David; Brown, Robert J.
Abstract Germinomas and embryonal carcinomas are central nervous system (CNS) germ cell tumors (GCT) that may overexpress the proto‐oncogene c‐KIT, a receptor tyrosine kinase, of which dasatinib is a potent inhibitor. This retrospective review presents the feasibility and tolerability of dasatinib administration in select patients with CNS germinoma. Between November 2008 and April 2010, six patients with newly diagnosed (n = 3) or recurrent (n = 3) CNS GCT were treated in an effort to avoid irradiation and/or delay recurrence. The daily doses administered were 100–170 mg/m2 with mostly grade 1–2 toxicities. Dasatinib may play a role in future treatment strategies for CNS GCT. Pediatr Blood Cancer 2013;60:E100–E102. © 2013 Wiley Periodicals, Inc.